Individual Risk Attitudes and the Composition of Financial Portfolios: Evidence from German Household Portfolios - Nataliya Barasinska; Dorothea Schäfer; Andreas Stephan (Quarterly Review of Economics and Finance, 2012)
This paper explores the relationship between the self-declared risk aversion of private investors and their propensity to hold incomplete portfolios of financial assets. The analysis is based on household survey data from the German Socioeconomic Panel (SOEP) that provides a reliable measure of individual attitudes toward financial risk. Our findings suggest that more risk averse households tend to hold incomplete portfolios consisting mainly of a few risk-free assets. We also find that the propensity to acquire additional assets is highly dependent on whether liquidity and safety needs are met.
Additional information: This is the postprint of an article published in the Quarterly Review of Economics and Finance 52 (2012), 1, p. 1-14, available online at: http://dx.doi.org/10.1016/j.qref.2011.10.001
Keywords: D14; G11; 330; private households; portfolio diversification; risk aversion; Sparen; Panel; Geldanlagen; Deutschland